Relation between digital innovation and industry 4.0: existing themes and emerging research trends - Gupta M.; Jauhar S.K.; Paul S.K.; Pratap S. (My University, 2025)
The primary objective of the research study is to investigate the influence of innovative digital tools and technologies in attaining the fundamental aspects of Industry 4.0, including automation, integration, traceability, flexibility, safety, and security. This study utilizes a systematic literature review, employing keyword search criteria to examine 187 relevant articles and evaluate the implementation and consequences of technologies, such as artificial intelligence, big data, cyber-physical systems, cloud computing, and digital twin, across a variety of Indian economic sectors, including retail, healthcare, manufacturing, agriculture, entertainment, and e-commerce. The study’s results indicate that digital technologies can improve parameters such as automation, transparency, integration, traceability, flexibility, safety, and security, while promoting sustainable development through reduced waste, operational costs, and time, and optimum resource utilization. The insights from this study will be helpful for future inquiries and economic initiatives, encouraging the adoption of digital innovations in fields such as women’s empowerment, public administration, and skill development. © The Author(s), under exclusive licence to Operational Research Society of India 2024.